Temporal Causality and Dynamics of Financial Development, Trade Openness, and Economic Growth in Vector Auto Regression (VAR) for Bangladesh, 1974-2003: Implication for Poverty Reduction - Hassan, A.F.M. Kamrul; Islam, M. Rafiqul (Journal of Nepalese Business Studies, 2007)
This paper examines whether financial development and openness to international trade can play any positive role in reducing poverty in Bangladesh through their growth enhancing effect. The paper takes granted that growth reduce poverty and makes econometric test to ascertain whether financial development and trade openness cause growth. Standard Granger-causality test is employed for this purpose. Variables are found first difference stationary without having any co-integrating relationship as reported by Johansen co-integration test. As such Granger-causality test is carried out in first difference VAR. The paper does not find any causal relationship between trade openness and growth, and financial development and growth. This implies that financial development and trade openness do not reduce poverty through their effect on growth. However, bi-directional causal link evidenced between financial development and trade openness indicates that these two can contribute to poverty reduction directly through their mutual effect on each other. Journal of Nepalese Business Studies Vol.2(1) 2005 pp.1-12